The Effectiveness of the Instagram Account @Pariaman.tourism as a Media of Tourism Information and Promotion in Kota Pariaman - Pradita, Dea Anandya; Yozani, Ringgo Eldapi (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2023)
The Tourism and Culture Office of Pariaman City designed a planning program with several stages, namely content creation, platform determination, program implementation, monitoring and the final stage of evaluating. This planning is carried out to maximize tourism-related information and promotions through media that are considered quite effective, so as to have an influence on the number of tourists visiting both on a national and international scale. The purpose of this study is to determine the extent to which the effectiveness of social media accounts can be a medium for fulfilling information and promoting tourism. This type of research is quantitative with a descriptive approach. The research population is Instagram followers @pariaman.tourism and a sample of 366 respondents. The results of the research on the effectiveness of communication on the Instagram account @pariaman.tourism seen from the theory of communication effectiveness according to Hardjana which consists of six indicators, obtained a value of 3.30 which is included in the very effective scale range. Thus, the Instagram account @pariaman.tourism is a very effective medium in conveying information and promotions about tourism in the city of Pariaman.